Ceinidae - Coleman, Charles Oliver (Zootaxa, 2009)
Ceina gerlachae sp. nov. is described. It differs in the habitus from the closely related Ceina carinata (Pirlot) in the rounded anterior process of pereonite 1, an upright carina on pleonite 1, a short process on pleonite 3 and a few characters on the maxillipeds.